No logo brands, globalization, resistance - Garner, Kelly; Klein, Naomi; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2003)
Using hundreds of media examples, No Logo shows how the commercial takeover of public space, destruction of consumer choice, and replacement of real jobs with temporary work (the dynamics of corporate globalization) impact everyone, everywhere. It also draws attention to the democratic resistance arising globally to challenge the hegemony of brands
Intro -- No space: new branded world -- No choice:brand bombing -- No jobs: the discarded factory -- No logo: anti-corporate activism & reclaiming the streets
Extras (9 min.) : Virgin stretches the brand ; Cool hunting & the cooptation of youth culture ; Branding & BMW films ; Coke vs. tape water ; Mickey Mouse goes to Haiti ; Benetton & political advertising ; Public vs. private
Based on the book : No logo / Naomi Klein
Running times 50 min. includes extras
Executive producer, Sut Jhally, Loretta Alper ; ditor, camera, Kelly Garner
Features : Naomi Klein
Keywords: International business enterprises -- Political aspects; International business enterprises -- Public opinion; Brand name products -- Political aspects; Brand name products -- Public opinion; Consumers' preferences